Indefinite eigenvalue problem with eigenparameter in the two boundary conditions - S. F. M. Ibrahim (International Journal of Mathematics and Mathematical Sciences)
The object of this paper is to establish an expansion theorem for a regular indefinite eigenvalue problem of second order differential equation with an eigenvalue parameter,λ in the two boundary conditions. We associated with this problem a J-selfadjoint operator with compact resolvent defined in a suitable Krein space and then we develop an associated eigenfunction expansion theorem.